How does organizational commitment in employees relate to work engagement in millennial employees in the era of the Fourth Industrial Revolution? - Jakayati, Novia; Prahara, Sowanya Ardi (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
The era of the Industrial Revolution 4.0 requires the world to continue to develop. This affects the performance of human resources at this time. Therefore, employees who are competent in their fields are needed. One of them is millennial generation employees who are known to be able to adapt and control technology. However, millennial employees have characteristics that make them quickly bored, so they easily decide to leave their jobs. This is undoubtedly related to the engagement of employees of the millennial generation. Therefore, millennial generation employees need organizational commitment; by committing, they can increase their sense of attachment to the company. The subjects in this study amounted to 60 millennial-generation employees with the characteristics of working for at least one year and aged between 21 and 41 years. The data collection method in this study used the Work Engagement Scale and the Organizational Commitment Scale. The data analysis technique used is product-moment correlation from Karl Pearson. The results of data analysis were obtained with the correlation coefficient value, which means there is a significant positive relationship between Organizational Commitment and Work Engagement.